CORRELATION BETWEEN THE KNOWLEDGE LEVEL OF MOTHER ON DENTAL HEALTH AND THE CARIES SEVERITY LEVEL OF CHILDREN IN BARITO KUALA - Galuh Dwinta Sari; Noor Mutiari Amalia; Isnur Hatta (Dentino : Jurnal Kedokteran Gigi, 2021)
Background: Dental and oral health is inseparable. Dental health problems can affect the growth and the development of children. Dental caries or cavity is one of the dental health problems that often find in children. The knowledge of mother on certain things underlies the formation of behavior that supports oral health in children. A mother is the closest person to child that holds a significant role to guide, educate, remind, and facilities children’s need for oral and dental health. Purpose: This research aims to analyze the relationship between maternal knowledge about dental health and the severity of caries in children in Barito Kuala Regency. Methods: This research is an observational analytic cross-sectional study. The number of samples was 32 respondents with random sampling. Data collection techniques used primary data in mothers and students of Nusa Indah Berangas Kindergarten, Alalak  SubDistrict. The measurement of knowledge level used a questionnaire that had been tested for validity and reliability while the measurement of caries severity was based on def-t index. Result:  Results of Spearman test showed (p <0.05) the direction of positive correlation. The worse the level of knowledge, the higher the severity of caries. The correlation coefficient was 0.599 (medium correlation strength). Conclusion: There is a correlation between maternal knowledge about dental health and the severity of caries in children aged 4-5 years at the Nusa Indah Berangas Kindergarten, Alalak SubDistrict, Barito Kuala Regency.